Study on Hemoglobin Concentration in Female Diabetic Patients - Hussain, Maria; Nessa, Akhtarun; Haque, AKM Nazmul; Nasreen, Shamima; Begum, Arifa; Parveen, Shahanaz; Bintay Ansari, Nahid; Muktadira, -; Naznin, Rubaiyat (Community Based Medical Journal, 2021)
Millions of people around the world are suffering from a destructive disease known as diabetes mellitus. In the present study hemoglobin concentration was estimated in female type 2 diabetes to observe the frequency of lowering hemoglobin level in these patients and to assess the incidence of anemia. This Descriptive type of cross sectional study was carried out in the Department of Physiology, Mymensingh Medical College, Mymensingh between the periods from July 2016 to June 2017. A total of 210 subjects were selected and were grouped as control group, Group I (70 healthy female of reproductive age, 21-45 years) and study group , Group II which was again subdivided to Group IIA (70 diabetic female of reproductive age , 21-45 years) and Group IIB (70 diabetic female of post-menopausal age, 45-70 years). Laboratory analysis of fasting serum glucose hemoglobin concentration was evaluated by the Cyanmethemoglobin (CMG) method. A comparison in hemoglobin concentration was done in between Group I and Group IIA and also in between Group IIA and Group IIB. The results were calculated and analyzed by using SPSS. For statistical analysis students unpaired 't' test was performed. The result showed that hemoglobin level was significantly decreased in the study group in comparison to the control group. It was concluded that type 2 diabetes is associated with decreased hemoglobin concentration leading to anemia. CBMJ 2020 January: Vol. 09 No. 01 P: 25-29